DIGITALISASI METODE PEMBAELAJARAN CASE METHOD SISTEM TELEKOMUNIKASI LANJUT - BONOK, ZAINUDIN; SAPUTRA, SUGIANTO (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2024)
Technological developments in the world of education and teaching require additional expertise from lecturers, especially in terms of digitizing learning materials and media. The literacy that teachers need is digitization or changing printed writing to be based on digital technology. This digital transformation process includes the integration of the latest technology into all aspects of life, including in learning contexts, both theoretical and practical. This research chose to use a case study design approach because it is appropriate in situations where the research questions relate to how or why a phenomenon occurs. A case study is the result of open research on a particular case. We conducted an open survey with students of the Electrical Engineering Undergraduate Study Program, Faculty of Engineering, Gorontalo State University about their satisfaction with the Advanced Telecommunication Systems course. This questionnaire consists of a list of questions or written statements with answer choices available in the question range 1-14. Respondents can only choose one of the available answer choices, which is called an answer choice. By understanding students as individuals in their uniqueness and in their entirety.. Data was collected from a survey conducted by Electrical Engineering for Advanced Telecommunication Systems students that focused on how the system will be impacted in the future. Prospective methods are used in areas such as economics, risk management, and strategic planning to predict future events. It uses historical data and data analysis to estimate potential future events. It uses historical data and data analysis to predict events that will occur in the future. Based on the results of the questionnaire for participants in advanced telecommunications systems courses, of the 8 who were willing to fill out the questionnaire, 80% strongly agreed with the digitalization of telecommunications systems method learning cases. carry on. 10% disagree and 10% disagree because of internet network problems. ABSTRAKPerkembangan Teknologi di dunia Pendidikan dan pengajaran membutuhkan keahlian tambahan dari dosen, terutama dalam hal digitalisasi materi dan media pembelajaran. Literasi yang diperlukan pengajar adalah digitisasi atau mengubah tulisan cetak menjadi berbasis teknologi digital. metode pembelajaran dengan Case Method. digitalisasi mengintegrasikan inovasi teknologi informasi Proses transformasi digital ini mencakup integrasi teknologi terkini ke dalam segala aspek kehidupan, termasuk dalam konteks pembelajaran baik teori maupun praktikum Penelitian ini memilih menggunakan pendekatan desain studi kasus karena sesuai dalam situasi di mana pertanyaan penelitian berkaitan dengan bagaimana atau mengapa suatu fenomena terjadi. Studi kasus yakni hasil dari suatu openelitian sebuah kasus tertentu . Kami melakukan survei terbuka kepada mahasiswa Prodi S1 Teknik Elektro Fakultas Teknik Universitas Negeri Gorontalo tentang kepuasan mereka dengan mata kuliah Sistem Telekomunikasi Lanjut. Kuisioner ini terdiri dari daftar pertanyaan atau pernyataan tertulis dengan pilihan jawaban yang tersedia dalam rentang pertanyaan 1-14. Responden hanya dapat memilih satu dari pilihan jawaban yang tersedia, yang disebut sebagai pilihan jawaban. Dengan memahami mahasiswa sebagai individu dalam keunikannya dan dalam keseluruhannya. Karena salah satu metode penelitian yang berbasis pada pemahaman dan perilaku manusia berdasarkan pada opini manusia di dalam ruang konteks yang telah ditentukan. Data dikumpulkan dari survei yang dilakukan oleh mahasiswa Teknik Elektro untuk Sistem Telekomunikasi Lanjut yang berfokus pada bagaimana sistem akan berdampak di masa depan. Berdasarkan hasil kuisioner peserta mata kuliah sistem telekomunikasi lanjut dari 8 yang bersedia mengisi kusioner, 80% sangat setuju dengan adanya digitalisasi pembelajaran case metdhod sistem telekomunikasi lanjut. 10 % kurang setuju dan 10 % tidak setuju karena adanya kendala jaringan internet.